The effect of evaluation in physical education on the attitudes of high school girls - Jones, Denise E. M.(Denise Elizabeth Magdalena) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1987.